No Connections, No Employment: Social Capital and Youth Graduate Unemployment in South Africa - Zethembe Mseleku (E-Journal of Humanities, Arts and Social Sciences)
South Africa continues to battle against the constantly increasing unemployment rate despite the major improvements in the massification of higher education. Young people, in particular, are at the receiving end of the stubborn unemployment problem, and the increasing graduate unemployment is a cause for concern. This paper thus explored the perspectives of unemployed young graduates regarding the association of nepotism, favoritism, and the struggle of young graduates to find employment in South Africa. The study employed the lens of social capital theory to explain the “connections phenomenon” in relation to graduate unemployment in South Africa. Primary qualitative data was solicited through face-to-face semi-structured interviews conducted with 30 graduates. The findings indicate that young graduates perceived nepotism and favoritism as significant factors that determine the probability of finding employment, particularly in South Africa’s public sector institutions. The findings revealed that the connections phenomenon in South Africa occurs through family members, relatives, friendships, political affiliations, and professional networks. Thus, graduates without connections, particularly from poor families, are disadvantaged in the labor market. This paper concluded that high unemployment is a driving force for nepotism and favoritism in South Africa’s labor market. Therefore, addressing nepotism and favoritism largely depends on increasing the labor force demand in South Africa.